Harnessing the power of seaweed: unveiling the potential of marine algae in drug discovery - Leonel Pereira; Ana Valado (Exploration of Drug Science)
Seaweeds, also known as marine algae, have gained attention as a promising source of bioactive compounds with potential applications in drug discovery. This review explores the emerging field of seaweed-based drug discovery and highlights the diverse range of bioactive compounds found in seaweeds, including polysaccharides, phlorotannins, pigments, and peptides. These compounds exhibit various pharmacological activities such as antioxidant, anti-inflammatory, antimicrobial, antiviral, and anticancer effects. Seaweeds have demonstrated particular promise in the areas of cancer research, with certain species showing potent antitumor properties. Additionally, their anti-inflammatory, antimicrobial, and neuroprotective potential has captured scientific interest in the treatment of chronic diseases and neurodegenerative disorders. However, challenges related to compound identification, extraction methods, scalability of seaweed cultivation, and understanding the mechanisms of action still need to be addressed. As researchers employ advanced technologies and dive deeper into the chemical composition of seaweeds, the untapped potential of these marine organisms in drug discovery awaits further exploration and holds significant promise for future therapeutic advancements.